The Impact of Compensation on Employees Engagement: Blom Bank in Jordan as a Case Study (The International Journal for Scientific Research, 2024)
The study aimed to identify the level of applying the required financial and non-financial compensation by BLOM BANK, as well as the level of employees’ engagement in BLOM BANK (Jordan) and the impact of financial and non-financial compensation on employees’ engagement in the researched bank. The study population included all the employees of the BLOM BANK branches in Jordan amounting to about (400) employees. A simple random sample of (200) employees was withdrawn from the population of the study. To achieve the objectives of the study, the researcher prepared a questionnaire to examine the variables of the study, which were distributed to the sample of the study, and all were valid for analysis. To analyze the collected data, the researcher used the statistical package for social sciences (SPSS).The study reached to a number of findings, most prominent of which are:1.     The level of applying the required financial and non-financial compensation by BLOM BANK’ (Jordan) employees was moderate.2.     The level of functional engagement of BLOM BANK’ employees was moderate.3.     There is a statistically significant impact at the level of significance (≥ α 0.05) for the direct and indirect financial compensation and non-financial (moral) compensation on the employees’ engagement of BLOM BANK (Jordan). The study suggested a number of recommendations, most important of which are:1.     The necessity of activating the positive aspects in the policy of financial and moral compensation in BLOM BANK (Jordan).2.     The need to review some aspects of the direct and indirect financial compensation, and the non-financial (moral) compensation in BLOM BANK (Jordan).
Keywords: Direct Financial Compensation; Indirect Financial Compensation; Moral Compensation; Employees Engagement